2019
DOI: 10.1101/755041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network analysis of mesoscale mouse brain structural connectome yields modular structure that aligns with anatomical regions and sensory pathways

Abstract: The Allen mesoscale mouse brain structural connectome is analysed using standard network methods combined with 3D visualizations. The full region-to-region connectivity data is used, with a focus on the strongest (top 40%) structural links. The spatial embedding of links and time evolution of signalling is incorporated, with twostep links included. Modular decomposition using the Infomap method produces 8 network modules that correspond approximately to major brain anatomical regions and system functions. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 79 publications
7
15
0
Order By: Relevance
“…1 suggest that some in links of low-medium weight are missing. A similar plot for mouse brain [Pailthorpe 2019] shows both distributions being quite similar - again suggesting some missing in-weight data here. This is consistent with sampling only 55 source nodes, being the 55, of the 116, anatomical areas used as tracer injection sites.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…1 suggest that some in links of low-medium weight are missing. A similar plot for mouse brain [Pailthorpe 2019] shows both distributions being quite similar - again suggesting some missing in-weight data here. This is consistent with sampling only 55 source nodes, being the 55, of the 116, anatomical areas used as tracer injection sites.…”
Section: Discussionsupporting
confidence: 54%
“…al. 2014, Pailthorpe 2019] and EM based results for worm [Varshnay 2011] and mouse retina [Helmstaedter et. al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Network analysis (Pailthorpe, 2024 ) of the marmoset cortical connectivity data, measured by retrograde tracers (Majka et al, 2016 , 2020 ), identified a significant 3D cluster in and around the pre-frontal cortex (pFC), which is examined here. The network analysis methods followed those used previously for the mouse retina (Pailthorpe, 2016 ) and the mouse brain (Pailthorpe, 2019 ). Previous studies of brain networks (Sporns and Kotter, 2004 ) generally focused on small motifs comprising 2, 3, or at most 4 nodes due to the combinatorial explosion in the number of possible configurations of larger clusters.…”
Section: Introductionmentioning
confidence: 99%